Teori Hukum tentang Pembedaan Pemaknaan Kerugian Negara dan Risiko Bisnis - Kiagoos Adhimas Muhamad Adhiperwira (UNES Law Review, 2023)
The ambiguity of state losses and business risks occurs because there are still differences of opinion between the status of SOE financial management as state losses or business risks. The current paradigm in Indonesia occurs because there is a Constitutional Court Decision regarding State Finances for the separation of state assets, especially in SOE. The different theory is that state losses are not the same as business risks. The management of state finances has a cost basis for carrying out social services and welfare that is oriented in the realm of public administration law, the responsibility is given to the executive branch in this case the President and the Minister of Finance in order to manage state finances whose funds will come from the state budget. The oversight function of public financial management is cost-oriented to carry out public services and the welfare of its oversight function to the DPR while separated state assets have an investment basis which in the event of a loss is a business risk that needs to be reviewed from the perspective of business judgment rules which are oriented in the realm of private law. the oversight function shifted from the Minister of Finance to the Minister of SOE, this is proven by the Minister of SOE being a representative of the State as the SOE Shareholder. Meanwhile, state losses that are oriented towards criminal acts of corruption or criminal law must fulfill elements of unlawful acts, such as bribery, and abuse of office for personal gain as stipulated in Law 20/2001.